Uwarunkowania cyrkulacyjne konwekcji w południowej Polsce - Poręba, Szymon (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
This work presents the influence of atmospheric circulation on CAPE values over southern Poland. The CAPE index is the one of most commonly used convection indicators. The research was based on a re-analysis from the NCEP/NCAR database, soundings and two atmospheric circulation classifications: Grosswetterlagen and T. Niedźwiedź. The research period included 13 years from 2000 to 2012 during which time the maximum CAPE value reached 3695 J/kg (derived by reanalysis) and almost 4450 J/kg (derived by sounding). According to Grosswetterlagen, the biggest average and maximum CAPE values over southern Poland occurred during three synoptic situations: Trough over Western Europe (TRW), Low over Great Britain (TB), Low over Central Europe (TM).
Keywords: atmospheric circulation; convection; CAPE; soundings